Amperometric enzyme sensor for the rapid determination of histamine - Torre, Ricarda (2020)
The concentration of histamine, a biogenic amine, in fish is considered a fish spoilage indicator. Therefore, the development of a rapid-response and portable tool that allows its on-site analysis is very interesting since the consumption of high amounts of histamine causes scombroid poisoning. Thus, in this work a simple enzymatic sensor for the determination of histamine, based on a screen-printed carbon electrode and the enzyme diamine oxidase, was developed. The enzyme was immobilized on the electrode surface through a simple cross-linking procedure employing glutaraldehyde and bovine serum albumin. Chronoamperometry was used as the detection technique; the sensor showed a short response time (60 s, -0.3 V) and the measurements were performed by only using 40 μL of sample solution. The sensor provides an useful linear range (between 1 and 75 mg L-1 in fish extract), excellent reproducibility (RSD = 2.6%) and is reusable for up to 7 measurements. The feasibility of the sensor was tested performing histamine analysis in fish extracts achieving recovery values of 103%.